Enoc, viajero celeste más allá de la muerte - autor, Sin (Revista de Filología Románica, 2006)
The Bible does not mention the death of Enoch, a fascinating character whom several Enochic traditions depict as revelator of heavenly secrets, inventor of the calendar and the astronomy, celestial scribe and voyager. The short biblical account in Genesis 5:21-24 shows that the span of his earthly life (equal in number to the days of the solar calendar) was considerably shorter than that of the rest of the antediluvian patriarchs and simply reports that «he was not; for God took him». Moreover, as it is twice recorded that «Enoch walked with God», apocalyptic speculations arose which resulted in a varied literary corpus centred around him from the 3rd century B.C. to the 5th / 6th century A.D. Apocalyptic works like 1 Enoch (Ethiopic), 2 Enoch (Slavonic) or 3 Enoch (Hebrew) record many additional topics about him such as, for instance, his heavenly tours. The legendary figure Enoch is taken through the heavenly realms and shown cosmic secrets; the fate of the dead in the underworld are also revealed to him.